Poesia em jogo : a ludificação do poema - Mendes, Israel (2016)
This work promotes a search of the structural relationship between poetry and play. Thus, a theoretical and literary pathway was mandatory. French Symbolism was the analytical starting point of this study, especially in the figures of Baudelaire, Rimbaud and Mallarmé. This last one, taken as the apex of the playful and experimental poetry of his time, was the greatest pillar of this approach. In addition, a playful pathway was also required, blending concepts and theories sourced from the game field. This search yet showcased the investigation of compelling issues such as hypertextuality, co-authorship and rewriting.